2019
DOI: 10.1038/s41698-019-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Precise definition of PTEN C-terminal epitopes and its implications in clinical oncology

Abstract: Anti-PTEN monoclonal antibodies (mAb) are arising as important tools for immunohistochemistry (IHC) and protein quantification routine analysis in clinical oncology. Although an effort has been made to document the reliability of tumor tissue section immunostaining by anti-PTEN mAb, and to standardize their IHC use in research and in the clinical practice, the precise topological and biochemical definition of the epitope recognized by each mAb has been conventionally overlooked. In this study, six commercial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 83 publications
(63 reference statements)
1
21
0
Order By: Relevance
“…In the cytoplasm, PTEN exists as a monomer and can even form a homodimer in vitro (Heinrich et al, 2015). The disordered CTT is key to the regulation of the monomeric PTEN state in the cytosol through the phosphorylation of the serine-threonine cluster (Ser380, Thr382, Thr383, and Ser385) located in it (Bolduc et al, 2013;Masson et al, 2016;Masson and Williams, 2020;Mingo et al, 2019;Vazquez et al, 2000). Cytosolic PTEN monomers exhibit a Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…In the cytoplasm, PTEN exists as a monomer and can even form a homodimer in vitro (Heinrich et al, 2015). The disordered CTT is key to the regulation of the monomeric PTEN state in the cytosol through the phosphorylation of the serine-threonine cluster (Ser380, Thr382, Thr383, and Ser385) located in it (Bolduc et al, 2013;Masson et al, 2016;Masson and Williams, 2020;Mingo et al, 2019;Vazquez et al, 2000). Cytosolic PTEN monomers exhibit a Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Previous PTEN studies showed that affinity to the membrane is reduced by the following: cancer-associated mutations (Masson and Williams, 2020) inhibit recruitment to the plasma membrane, thus abolishing its interactions with phospholipids (Nguyen et al, 2015); phosphorylation of the CTT serine-threonine cluster impairs PTEN membrane binding ability, resulting in a closed protein conformation (Bolduc et al, 2013;Malaney et al, 2013;Masson and Williams, 2020;Rahdar et al, 2009;Ross and Gericke, 2009); CTT deletion decreases protein stability leading to tumor development (Georgescu et al, 1999;Sun et al, 2014); and a mutation in the PBD (K13E) leads to PTEN inactivation (Masson and Williams, 2020;Nguyen et al, 2015;Walker et al, 2004). In the cytosol, monomeric PTEN is in the inactive state with its PBD bound to the phosphatase domain and the phosphorylated CTT interfering with the membrane binding interface (Bolduc et al, 2013;Chen et al, 2016;Malaney et al, 2013;Masson et al, 2016;Masson and Williams, 2020;Mingo et al, 2019;Rahdar et al, 2009;Ross and Gericke, 2009;Vazquez et al, 2000) (Figure 7), whereby the inactive, autoinhibited PTEN is in the "closedclosed" conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell nuclei were stained with Hoechst 33342 (ThermoFisher Scientific). For immunoblot, COS-7 cells were processed as described [ 26 ]. Briefly, cells were washed with PBS and lysed in ice-cold M-PER lysis buffer (ThermoFisher Scientific) supplemented with PhosSTOP phosphatase inhibitor and complete protease inhibitor cocktails (Roche).…”
Section: Methodsmentioning
confidence: 99%